Get to Know More About “The Power of Mama”, Community – Based Disaster Preparedness and Female Heroes for Indonesia’s Borneo Forests - Nabilla, Nada; Hidayat, Muhamad (SEAN Institute, 2024)
Indonesia has unique astronomic location which positioning in the south of the equator exerts substantial influence on various facest of the region, including weather patterns, land and forest arrangement, economic dynamics, societal structures, and disaster vulnerability. The country’s reputation as the “world’s lungs” stems from its high precipitation levels, profoundly impacting the expanse of forests. Conversely, the equatorial dry season can usher in extreme high temperatures, giving rise to hazards like forest and land fires, as exemplified in the protected forest areas of Ketapang Village, West Kalimantan. Consequently, comprehensive mitigation strategies involving both structural and non-structural approaches are imperative, engaging a multitude of stakeholders. Notably, women’s leadership roles play a pivotal part in disaster risk management and decision-making, given their influential contributions to rural community development. Furthermore, this initiative aims to curtail the disproportionate toll that disasters, and their aftermath, impose on women. In response to these circumstances, YIARI has instituted “The Power of Mama,” a women’s community initiative spearheaded by homemakers in Ketapang Village, focused on addressing the wildfire disaster risk in Borneo’s Protected Forest, Kalimantan. This analysis of women’s empowerment in forest and land fire disaster governance in Kalimantan draws upon semi-srtuctured qualitative interviews and insights gleaned from an extensive literature review.